2011
DOI: 10.1002/jat.1669
|View full text |Cite
|
Sign up to set email alerts
|

In vitro toxicity of aflatoxin B1 and its photodegradation products in HepG2 cells

Abstract: The effects of aflatoxin B1 (AFB1) were studied using the HepG2 cell line. Cytotoxicity, apoptosis and p53 expression were assessed after exposure to different concentrations of AFB1 (0-100 μM) and its two types of degradation products, namely the mixtures of photodegradation products in water (Pw) and the mixtures of photodegradation products in peanut oil (Po) for different time periods (0, 24, and 48 h). After exposure of the HepG2 cells to these compounds for different times and concentrations, the cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…They also investigated the toxicity of photodegradation products of AFB 1 in water (P w ) and peanut oil (P O ) on HepG2 cells, and found the cytotoxicity of P w and P O decreased about 40 and 100%, respectively. Their results showed that the P w is less toxic than AFB 1 , and the P O has almost no toxicity (Liu et al, 2012). According to the results from the Ames test and cytotoxicity of HepG2 cells, we have obtained similar results after being irradiated of AFB 1 in peanut oil using a photodegradation reactor .…”
Section: Safety Of Aflatoxins After Uv Irradiationsupporting
confidence: 82%
“…They also investigated the toxicity of photodegradation products of AFB 1 in water (P w ) and peanut oil (P O ) on HepG2 cells, and found the cytotoxicity of P w and P O decreased about 40 and 100%, respectively. Their results showed that the P w is less toxic than AFB 1 , and the P O has almost no toxicity (Liu et al, 2012). According to the results from the Ames test and cytotoxicity of HepG2 cells, we have obtained similar results after being irradiated of AFB 1 in peanut oil using a photodegradation reactor .…”
Section: Safety Of Aflatoxins After Uv Irradiationsupporting
confidence: 82%
“…These changes were reversal after AFB1 withdrawal. This AFB1-induced cellular degeneration has been attributed to its apoptotic effect in several mammalian tissues, such as kidney and liver (Lei et al, 2013;Liu et al, 2012). AFB1-induced cellular apoptosis was also reported in the central and peripheral nervous system as a result of alterations in the neurochemical levels following repeated administration of aflatoxin (Ikegwuonu, 1983).…”
Section: Discussionmentioning
confidence: 95%
“…Ultraviolet (UV) irradiation as a non-thermal technology is widely applied in the food industry for disinfection, which is also considered to be practical and cost-effective method to reduce aflatoxins for its photosensitive properties [8]. As an effective physical method, many studies have been done to investigate the efficiency of UV irradiation, the degradation product of aflatoxins, the safety of degradation products and quality of foods after being irradiated [9,10,11,12,13,14]. It was found that aflatoxins could be efficiently degraded by UV irradiation, and the degradation efficiency varied with the differences of irradiation conditions [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, most studies were carried out on the Ames test and cytotoxicity of HepG2 cells of AFB 1 products after irradiation [10,13,16,17]. The toxicities of the photodegradation products of AFB 1 in water and peanut oil on HepG2 cells were investigated, and it was found that the cytotoxicity of products of AFB 1 in water decreased 40%, while that of products of AFB 1 in peanut oil reduced about 100% [13].…”
Section: Introductionmentioning
confidence: 99%